Establishment of an Enzyme Immunoassay Using Monoclonal Antibody (HG1‐219) and Its Application for the Diagnosis of Hepatocellular Carcinoma - Hada, Toshikazu (Jpn J Cancer Res, 1992)
A monoclonal antibody (MoAb HG1‐219) against a human gastric cancer cell line (HuG‐1) and its shedding antigen (HG1‐219 Ag) was generated and a solid‐phase sandwich enzyme immunoassay (EIA‐219) was developed. The mean serum HG1‐219 Ag concentration in normal individuals was 30.5 ± 14.5 U/ml measured by EIA‐219. When the mean + 3 SD of the antigen concentration in normal individuals was used as a cut‐off level, 4.3% (2/47) of patients with chronic hepatitis, 9.1% (4/44) of cirrhotic patients and 37.5% (18/48) of patients with hepatocellular carcinoma (HCC) had HG1‐219 Ag above the cut‐off value. The positive rates of a‐fetoprotein (AFP) (> 400 ng/ml) and protein induced by vitamin K absence or antagonist‐II (PIVKA‐II) for HCC were 26.7% (12/45) and 33.3% (12/36), respectively. There was no significant correlation between HG1–219 Ag and AFP or PIVKA‐II in patients with HCC. The combination assay of EIA‐219, AFP and PIVKA‐II for HCC gave the positive rate of 75% (27/36). The effect of periodic acid on the HG1‐219 Ag and the inhibition of EIA‐219 by CA 19–9 suggest that the epitope of HG1–219 Ag is a suger chain similar to CA 19–9.